Securitization of human rights North Korean refugees in East Asia - Kim, Mikyoung; Kim, Mikyoung (Praeger, 2012)
"This important book focuses on North Korean refugee human rights issues--a topic largely ignored in favor of addressing North Korea's domestic politics and deterrence of Pyongyang's nuclear threat"